Sampling and analysis of iron, steel and other ferrous metals. Methods of analysis. Determination of molybdenum. Molybdenum oxide and high grade molybdenite ores: gravimetric method Part 3.19.3, (15th June 1992) - British Standards Institution,
No abstract available